Inter-Organelle Crosstalk in Oxidative Distress: A Unified TRPM2-NOX2 Mediated Vicious Cycle Involving Ca2+, Zn2+, and ROS Amplification - Esra Elhashmi Shitaw; Maali AlAhmad; Asipu Sivaprasadarao (Antioxidants)
Reactive oxygen species (ROS) are critical signalling molecules, but their overproduction leads to oxidative stress (OS), a common denominator in the pathogenesis of numerous non-communicable diseases (NCDs) and aging. General antioxidant therapies have largely been unsuccessful, highlighting the need for a deeper understanding of ROS amplification mechanisms to develop targeted interventions. This review proposes a unified, self-amplifying “vicious cycle” of inter-organelle crosstalk that drives pathological ROS elevation and cellular damage. We outline a pathway initiated by extracellular stressors that co-activate plasma membrane TRPM2 channels and NADPH oxidase-2. This synergy elevates cytoplasmic Ca2+, leading to lysosomal dysfunction and permeabilization, which in turn releases sequestered Zn2+. Mitochondrial uptake of this labile Zn2+ impairs electron transport chain function, particularly at Complex III, resulting in mitochondrial fragmentation, loss of membrane potential and a burst of mitochondrial ROS (mtROS). These mtROS diffuse to the nucleus, activating PARP-1 and generating ADPR, which further stimulates TRPM2, thereby perpetuating the cycle. This “circular domino effect” integrates signals generated across the plasma membrane (Ca2+), lysosomes (Zn2+), mitochondria (ROS) and nucleus (ADPR), leading to progressive organelle failure, cellular dysfunction, and ultimately cell death. Understanding and targeting specific nodes within this TRPM2-NOX2-Ca2+-Zn2+-mtROS-ADPR axis offers novel therapeutic avenues for NCDs by selectively disrupting pathological ROS amplification while preserving essential physiological redox signalling.